Case report: A successfully treated case of community-acquired urinary tract infection due to Klebsiella aerogenes in Bangladesh - Mazumder, Razib; Hussain, Arif; Bhadra, Bithika; Phelan, Jody; Campino, Susana; Clark, Taane G.; Mondal, Dinesh (Frontiers in Medicine, 2023)
Klebsiella aerogenes, a nosocomial and pathogenic bacterium, is increasingly associated with extensive drug resistance and virulence profiles. It is responsible for high morbidity and mortality. This report describes the first successfully treated case of community-acquired urinary tract infection (UTI) in an elderly housewife suffering from Type-2 diabetes (T2D) from Dhaka, Bangladesh. The patient was empirically treated with intravenous ceftriaxone (500 mg/8 hours), but she did not respond to the treatment. The urine culture and sensitivity tests, coupled with bacterial whole-genome sequencing (WGS) and analysis, revealed the bacteria to be K. aerogenes which was extensively drug-resistant but demonstrated susceptibility to carbapenems and polymyxins. Based on these findings, meropenem (500 mg/8 hours) was administered to the patient, who then responded to the treatment and recovered successfully without having a relapse. This case raises awareness of the importance of diagnosis of not-so-common etiological agents and the importance of correct identification of the agent and appropriate antibiotic therapy. In conclusion, correctly identifying etiological agents of UTI by using WGS approaches that are otherwise difficult to diagnose could help improve the identification of the disease-causing agents and management of infectious diseases.